MARK-AGE biomarkers of ageing. (November 2015) - Bürkle, Alexander; Moreno-Villanueva, María; Bernhard, Jürgen; Blasco, María; Zondag, Gerben; Hoeijmakers, Jan H.J.; Toussaint, Olivier; Grubeck-Loebenstein, Beatrix; Mocchegiani, Eugenio; Collino, Sebastiano; Gonos, Efstathios S.; Sikora, Ewa; et al.
Highlights: MARK-AGE was a large-scale integrated project supported by the European Commission. About 3200 subjects were enrolled in this Europe-wide population study. The MARK-AGE Consortium comprised 26 European research partners including companies. MARK-AGE aimed at identifying a powerful set of biomarkers of human ageing. Biomarkers assessed in MARK-AGE included classical, new and novel ones. Abstract: Many candidate biomarkers of human ageing have been proposed in the scientific literature but in all cases their variability in cross-sectional studies is considerable, and therefore no single measurement has proven to serve a useful marker to determine, on its own, biological age. A plausible reason for this is the intrinsic multi-causal and multi-system nature of the ageing process. The recently completed MARK-AGE study was a large-scale integrated project supported by the European Commission. The major aim of this project was to conduct a population study comprising about 3200 subjects in order to identify a set of biomarkers of ageing which, as a combination of parameters with appropriate weighting, would measure biological age better than any marker in isolation.